Associations of Hydroxychloroquine Use With Lipid Profiles in Rheumatoid Arthritis: Pharmacologic Implications. Issue 11 (November 2014) - Kerr, Gail; Aujero, Mireille; Richards, John; Sayles, Harlan; Davis, Lisa; Cannon, Grant; Caplan, Liron; Michaud, Kaleb; Mikuls, Ted
<x xml:space="preserve">Abstract</x> Objective To evaluate the association of hydroxychloroquine (HCQ) use with lipid profiles in a Veterans Affairs Rheumatoid Arthritis (VARA) cohort. Methods Lipid profiles in HCQ users were compared with HCQ nonusers, adjusting for potential confounders (age, sex, race, disease activity, prednisone, disease‐modifying antirheumatic drugs, diabetes mellitus, and statin use). Applying current National Cholesterol Education Program Adult Treatment Panel III (NCEP‐ATP III) guidelines for reduction of cardiovascular disease (CVD) events risk, the frequency of target lipid profiles with HCQ status was evaluated. Varied periods of HCQ exposure were compared to ascertain pharmacologic associations with lipid values. CVDs were compared between HCQ users and nonusers. Results In an elderly, predominantly male VARA cohort, 1, 011 patients had lipid profiles; 787 patients (77.8%) were white. Statin use was recorded in 11.6% of patients, diabetes mellitus in 33.5%, and CVD in 31.2%. HCQ users (n = 150) were older, had longer rheumatoid arthritis (RA) disease duration, and had lower disease activity. Optimum lipid profiles, including total cholesterol:high‐density lipoprotein (HDL) and HDL:low‐density lipoprotein ratios (P ≤ 0.001), were more frequent in HCQ users, with the exception of HDL (P = 0.165), and persisted in multivariate analyses. Similarly, more HCQ users had NCEP‐ATP III target levels. Varied periods of HCQ exposure suggested lipid changes to occur early, but lost within a year of drug discontinuation. HCQ users had less prevalent CVD. Conclusion In RA patients, HCQ use of at least 3 months' duration was associated with better lipid profiles irrespective of disease activity or statin use. Given the increased CVD risks in RA and the relative low cost and toxicity of HCQ, continued use, regardless of treatment regimen, should be considered.